Correction: The effect of single and repeated doses of rivastigmine on gastric myoelectric activity in experimental pigs. - Chrysostomi Christina Tsianou; Jaroslav Kvetina; Vera Radochova; Darina Kohoutova; Stanislav Rejchrt; Martin Valis; Jana Zdarova Karasova; Ilja Tacheci; Veronika Knoblochova; Ondrej Soukup; Jan Bures (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0286386.].